An Exploration Collective Bargaining Units in the Public Service - Bodilenyane, Keratilwe; I. Ukpere, Wilfred; Mabaso, Calvin (Journal of Ecohumanism, 2025)
Bargaining units and rights are the basis for collective bargaining. The aspect of collecting bargaining unit is intimately related to the aspect of bargaining rights and collective bargaining coverage. Workers with bargaining rights might not be included in the available bargaining units. However, employees that are not part of the available bargaining units, with or without negotiating rights; may still be impacted by default extension mechanism through the erga omnes effect (towards all effect). Thus, the primary goal of this study was to explore the current bargaining units and negotiating rights for various groups of public sector employees. It is important for parties to understand the breadth of their negotiating rights and units, as well as the ways in which they can extend them, such as through agency shop agreements and erga omnes processes. The study was premised on the pluralist approach to understand the agreements for bargaining units and rights. The study was qualitative in nature, to gather participants experiences, opinions, knowledge about the phenomenon of interest. Data was collected from a sample of fifteen purposively selected participants from the public service. Thematic analysis through the help of ATLAS. Ti. was used for data analysis. The study found that all public service employees save for the disciplined forces have bargaining rights. It was also discovered that, even though all public servants have these rights, only those in D1 scale are covered by the current bargaining unit. Employees on salary scales E and F are not included in the bargaining unit, because they are classified as management. It was also evident that the workers that are not part of the bargaining units are covered by collective bargaining agreements through default erga omnes effect of collective bargaining agreement. The study therefore recommends clear provisions for bargaining rights and units.